Poor treatment outcomes and associated factors among hospitalized patients with stroke at Hiwot Fana Comprehensive Specialized Hospital, eastern Ethiopia - Ayele, Zerihun Abera; Molla, Sisay; Ahmed, Aliyi; Worku, Teshager; Bezabih, Addisu Seneshaw; Mamo, Biniyam Tedla (Frontiers in Stroke, 2023)
Background: Stroke is a significant health problem in both industrialized and developing nations. It is the world's second leading cause of death worldwide. Stroke incidence, prevalence, and death rates have grown internationally, with low-and middle-income nations suffering the greatest proportion of the burden. Stroke is a leading cause of long-term physical impairment, affecting a person's quality of life, societal engagement, independence, emotions, and productivity. Objective: To determine the magnitude and factors associated with poor treatment outcomes in hospitalized adult patients with stroke. Methods: A hospital-based cross-sectional study was conducted from January 2019-June to 2021 in stroke patients admitted to the Hiwot Fana Comprehensive Specialized Hospital. This study included 290 patient charts. Data were collected by reviewing the medical charts using a well developed data abstraction form. Data were entered into Epi-Data version 3.2 and exported to SPSS version 25.0. Descriptive statistics were used to describe study variables. Additionally, bivariable and multivariable logistic regression analyses were used to identify factors associated with poor stroke treatment outcomes. Statistical significance was set to declare statistical significance. Results: Among 290 enrolled patients, 172 (59.3 %) had poor stroke treatment outcomes. The mean age of the patients was 54.7(±SD:16.1) years and more than half 182(62.8%) of the participants were males. The overall average length of stay hospital Stays in stroke patients was 8±3.3 days. Age of 45-64 years (AOR:2.17, 95% CI: 1.06, 4.41), aspiration pneumonia (AOR:2.13, 95%CI: 1.06, 4.26), SBP ≥140 mmHg/dl (AOR:2.35, 95%CI: 1.24, 4.47), GCS of <8 (AOR:7.26, 95%CI: 3.82, 13.8), and serum creatinine level of ≥1 mg/dl (AOR:2.73, 95%CI: 1.46, 5.10) were significantly associated with poor treatment outcome in adult stroke patients. Conclusion: Six out of ten stroke patients had poor treatment outcomes. Age between 45 and 65 years, uncontrolled hypertension, aspiration pneumonia, low Glasgow coma scale at admission, and renal injury were identified as significantly associated with poor treatment outcomes in stroke patients.